2014
DOI: 10.1016/j.celrep.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Position and Morphology of Committed Precursor Cells in the Zebrafish Retina Adapt to Architectural Changes upon Tissue Maturation

Abstract: The development of complex neuronal tissues like the vertebrate retina requires the tight orchestration of cell proliferation and differentiation. Although the complexity of transcription factors and signaling pathways involved in retinogenesis has been studied extensively, the influence of tissue maturation itself has not yet been systematically explored. Here, we present a quantitative analysis of mitotic events during zebrafish retinogenesis that reveals three types of committed neuronal precursors in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 29 publications
7
104
0
1
Order By: Relevance
“…To test this notion, we performed HS on transgenic embryos at 48 hpf. At this stage, neurogenesis peaks, and only few proliferative divisions remain (Weber et al, 2014). Indeed, in these fish, retinal development was not significantly impaired: all retinal layers were formed, largely resembling control retinae, and only minor defects could be observed ( Figures 6I [N amplification is cell proliferation.…”
Section: Centriole Amplification Affects the Proliferative Phase Of Rmentioning
confidence: 91%
See 1 more Smart Citation
“…To test this notion, we performed HS on transgenic embryos at 48 hpf. At this stage, neurogenesis peaks, and only few proliferative divisions remain (Weber et al, 2014). Indeed, in these fish, retinal development was not significantly impaired: all retinal layers were formed, largely resembling control retinae, and only minor defects could be observed ( Figures 6I [N amplification is cell proliferation.…”
Section: Centriole Amplification Affects the Proliferative Phase Of Rmentioning
confidence: 91%
“…Crossing OS-Plk4 fish to transgenic lines labeling both early (Ath5-gapRFP marker for retinal ganglion and photoreceptors) and later-born neurons (Ptf1A-GFP marker for amacrine and horizontal cells and Vsx1-GFP marker for bipolar cells) (Weber et al, 2014) revealed that OS-Plk4-expressing cells were able to differentiate into all neuronal subtypes (Figures 6E and 6F). To test whether this was also the case upon mosaic expression, we injected the HS-OS-Plk4 construct together with the HS-H2B-GFP to label Plk4-expressing cells.…”
Section: Centriole Amplification Affects the Proliferative Phase Of Rmentioning
confidence: 94%
“…Spatial restrictions due to the maintained presence of intact photoreceptors following inner retinal cell death by ouabain exposure could explain the relatively lower migration potential of Müller glia nuclei into the ONL compared to the light-damaged retina lacking photoreceptors. Similarly, NPC divisions in the developing retina change from apical to non-apical at the onset of ONL formation (Weber et al 2014), supporting that cell density restrictions at least partially determine the position of mitosis.…”
Section: Müller Glia Inmmentioning
confidence: 96%
“…18 , which has previously been used to inhibit in vivo cell proliferation in the embryonic retina 19 . In BI2536-treated brains, the nuclear density rostral to the OT and thus the cell density gradient was significantly decreased compared to controls, particularly at later stages (Fig.…”
Section: A B) (See Online Methods For Details)mentioning
confidence: 99%
“…2e). To test if local cell densities drive the evolution of the stiffness gradient during OT turning, we repeated both nuclear staining and tiv-AFM measurements on embryos treated with the mitotic blocker BI253618 , which has previously been used to inhibit in vivo cell proliferation in the embryonic retina 19 . In BI2536-treated brains, the nuclear density rostral to the OT and thus the cell density gradient was significantly decreased compared to controls, particularly at later stages (Fig.…”
mentioning
confidence: 99%